2021
DOI: 10.1080/21645515.2021.1953349
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Harada disease-like uveitis after quadrivalent human papillomavirus vaccination: a case report

Abstract: This article describes a patient who developed Harada disease-like uveitis after quadrivalent human papillomavirus (HPV4) vaccination and experienced resolution without any systemic treatment. To achieve this aim, a case report and a review of related literature on HPV vaccination causing uveitis were conducted. The results of this study show a diagnosis of Harada disease-like uveitis after HPV4 vaccination based on the vaccination history, clinical symptoms, and multimodal imaging. Resolution without any syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Except for one unreported case [35], approximately 42.9% (three out of seven) of patients exhibited systemic symptoms such as fever, hearing loss, sore throat, headache, and joint pain [33][34][35]. With an average follow-up period of 1.2 years, vision completely recovered in five patients following corticosteroid treatment [21][22][23]34,35], including one patient who recovered with eyedrops alone [21]. However, some patients experience prolonged effects, such as recurrent leakage [33] (Figure 1) and extensive macular scarring [32].…”
Section: Human Papillomavirus (Hpv) Vaccinementioning
confidence: 95%
See 4 more Smart Citations
“…Except for one unreported case [35], approximately 42.9% (three out of seven) of patients exhibited systemic symptoms such as fever, hearing loss, sore throat, headache, and joint pain [33][34][35]. With an average follow-up period of 1.2 years, vision completely recovered in five patients following corticosteroid treatment [21][22][23]34,35], including one patient who recovered with eyedrops alone [21]. However, some patients experience prolonged effects, such as recurrent leakage [33] (Figure 1) and extensive macular scarring [32].…”
Section: Human Papillomavirus (Hpv) Vaccinementioning
confidence: 95%
“…After conducting a comprehensive review, a total of 51 reported cases (involving 61 patients), spanning from 1978 to 2023, have been associated with uveitis following various vaccinations (Table 1), including 4 case reports (5 patients) related to hepatitis B virus (HBV) vaccination [28][29][30][31]; 7 case reports (8 patients) related to human papillomavirus (HPV) vaccination [21][22][23][32][33][34][35]; 16 cases (18 patients) regarding uveitis after influenza vaccination [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]; 3 cases (4 patients) related to measles-mumps-rubella (MMR) vaccination [52][53][54]; 12 cases (16 patients) related to varicella zoster virus (VZV) vaccination [24][25][26][27][55][56][57][58][59][60][61][62]; 4 cases (5 patients) for yellow fever [63][64]…”
Section: General Analysis Regarding Cases Of Uveitis Post-vaccinationmentioning
confidence: 99%
See 3 more Smart Citations